INDISCIPLINA ŞCOLARĂ PRIN NONIMPLICAREA ELEVILOR - USM ADMIN (Moldova State University, 2010)
Scholar discipline represents one of the most important components of didactic activities, which can create the premises for pupils' success and their effective integration in scholar and social life. This is the reason for what professors pay more attention to scholar discipline and they appreciate those pupils who have a moral, responsible or pacifist behavior in school. The majority of professors are very disturbed by those pupils who have an aggressive or violent behavior and try to find different solutions in this sense. But not so many teachers try to do something with pupils who refuse to involve in didactic or extra-didactic activities and have a passive behavior, because they do not disturb the learning process. In this paper we intend to discuss about this kind of pupils and to present the risks of this non-active behavior for their development.